PENGARUH MEDIA MAKET PLAYDOUGH TERHADAP KECERDASAN VERBAL LINGUISTIK ANAK USIA 5-6 TAHUN: Aa Mursaluna, Susi Herlinda, Nopa Wilyanita - Mursaluna, Aa; Herlinda, Susi; Wilyanita, Nopa (P3M STKIP 'Aisyiyah Riau, 2024)
The purpose of this study was to determine whether playdough mock-up media influences verbal linguistic intelligence for children aged 5-6 years in TK Negeri Pembina 2 Pekanbaru. The research method that the researchers used is Quasi experiment and Nonequivalent Control Group Design. There are two classes used, namely the control class and the experimental class, where each class is carried out in 2 stages namely, the pretest stage (before being treated) and the posttest stage (after treated). The research sample of 30 children, 15 children each. From the test results using SPSS Windows ForVer 17, obtained sig 0.185 statistics is much greater than 0.05 (0.185> 0.05), thus it can be concluded that the research data is homogeneous. Based on the